STUDY OF EFFECTIVENESS OF SHELTERING FROM RADIATION EXPOSURE DUE TO ACCIDENTAL RELEASE OF RADIOACTIVITY. Issue 8 (18th June 2022) - Singh, Ashish Kumar; Dey, Riya; Deokar, U V; Ganesh, G; Kulkarni, M S; Anand, S
Abstract: Sheltering is one of the important protective actions as a part of emergency response during the early phases of an accident—mostly precautionary in nature. Sheltering via structural shielding reduces the direct exposure from plume/cloud shine and ground shine doses as well as the airborne radioactivity concentration and hence inhalation dose. The present study was aimed at estimating the shielding factor in the case of Indian houses for external exposure pathways using the FLUKA Monte Carlo based radiation transport code. Furthermore, the dose reduction factor due to exposure from the inhalation pathway was estimated using an indoor aerosol model. These factors were assessed for the three major types of dwellings, and they provided important inputs for decision-making for sheltering or evacuation in case of any sudden release of radionuclides into the environment.